1972
DOI: 10.1073/pnas.69.10.3033
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide Sequence at the Binding Site for Coat Protein on RNA of Bacteriophage R17

Abstract: The Coat protein of RNA bacteriophages functions as a repressor of translation of the cistron coding for RNA synthetase (the phage-coded subunit of the RNA replicating enzyme) (1-8).Isolated RNA and coat protein can interact to form two kinds of complexes: Complex I in which a few molar equivalents of coat protein [one (9)-six (10) ] bind to one equivalent of RNA leading to formation of a complex that sediments at the same rate as free RNA, and Complex II in which about 180 coat-protein molecules bind to one m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
77
0

Year Published

1983
1983
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(78 citation statements)
references
References 31 publications
1
77
0
Order By: Relevance
“…RaPID uses a novel fusion protein (MS2-CP-GFP-SBP) that possesses three relevant functional domains: (1) an amino terminal MS2-CP moiety that shows high affinity to the MS2L RNA aptamer (Bernardi and Spahr 1972;Valegard et al 1994); (2) a GFP reporter that allows for visualization of its intracellular localization in vivo and for protein detection in blots using anti-GFP antibodies; and (3) a carboxy-terminal SBP epitope that allows for specific high-affinity interactions with streptavidin-conjugated matrices (Keefe et al 2001). Together, the CP and GFP domains allow for visualization of the intracellular localization of MS2L-tagged mRNAs of interest (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…RaPID uses a novel fusion protein (MS2-CP-GFP-SBP) that possesses three relevant functional domains: (1) an amino terminal MS2-CP moiety that shows high affinity to the MS2L RNA aptamer (Bernardi and Spahr 1972;Valegard et al 1994); (2) a GFP reporter that allows for visualization of its intracellular localization in vivo and for protein detection in blots using anti-GFP antibodies; and (3) a carboxy-terminal SBP epitope that allows for specific high-affinity interactions with streptavidin-conjugated matrices (Keefe et al 2001). Together, the CP and GFP domains allow for visualization of the intracellular localization of MS2L-tagged mRNAs of interest (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the bacteriophage R17 coat protein recognizes a hairpin containing the ribosome binding site for the phage replicase (22). Also, viral RdRps replicating full-length products from linear templates have been shown to require various structures on the 3Ј end of the RNA template to initiate accurate synthesis (23)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…Although translational autoregulation has been described in prokaryotic systems (2,5), TS mRNA represents the first eukaryotic mRNA whose regulation is controlled in such a fashion. Furthermore, we demonstrated that incubation of TS protein with either the nucleotide substrate dUMP or the inhibitor 5-fluoro-dUMP repressed its inhibitory effect on TS mRNA translation.…”
mentioning
confidence: 99%